Revitalisasi Kompetensi Tenaga Kerja Bongkar Muat di Pelabuhan Cirebon - Eka Sukmawati; Johanes O.W Hitalessy; Achmad Hidayat; Muchlis Imanullah Arief (Institut Transportasi dan Logistik Trisakti, 2021)
The purpose of this study was to determine the competence and performance of the loading and unloading workforce to improve loading and unloading services at the Port of Cirebon. The research method uses qualitative methods through Importance Performance Analysis. Data collection techniques are direct observation, in-depth interviews, literature studies, focus group discussions, triangulation, documentation, and participation. The results of the study indicate that the performance of loading and unloading workers at the Port of Cirebon towards efforts to improve performance for unloading workers is currently considered not in accordance with the expectations of the Unloading Workers Cooperative and also service users, while the competencies possessed by unloading workers Loading at the Port of Cirebon has not been fully used to improve performance for the Unloading Workers at the Port of Cirebon, and also the facilities owned by the Port of Cirebon still need to be improved in order to obtain smoothness, speed, security and safety to support the loading and unloading of goods. from and to ships at Cirebon Harbor.